Cotrimoxazole prophylaxis and antiretroviral therapy: an observational cohort study in China - Wei Cheng; Yasong Wu; Yi Wen; Ye Ma; Decai Zhao; Zhihui Dou; Weiwei Zhang; Marc Bulterys; Fujie Zhang (Bulletin of the World Health Organization)
Objective To assess if cotrimoxazole prophylaxis administered early during antiretroviral therapy (ART) reduces mortality in Chinese adults who are infected with human immunodeficiency virus (HIV). Methods We did a retrospective observational cohort study using data from the Chinese national free antiretroviral database. Patients older than 14 years who started ART between 1 January 2010 and 31 December 2012 and had baseline CD4+ T-lymphocyte (CD4+ cell) count less than 200 cells/µL were followed until death, loss to follow-up or 31 December 2013. Hazard ratios (HRs) for several variables were calculated using multivariate analyses. Findings The analysis involved 23 816 HIV-infected patients, 2706 of whom died during the follow-up. Mortality in patients who did and did not start cotrimoxazole during the first 6 months of ART was 5.3 and 7.0 per 100 person–years, respectively. Cotrimoxazole was associated with a 37% reduction in mortality (hazard ratio, HR: 0.63; 95% confidence interval, CI: 0.56–0.70). Cotrimoxazole in addition to ART reduced mortality significantly over follow-up lasting 6 months (HR: 0.65; 95% CI: 0.59–0.73), 12 months (HR: 0.58; 95% CI: 0.49–0.70), 18 months (HR: 0.49; 95% CI: 0.38–0.63) and 24 months (HR: 0.66; 95% CI: 0.48–0.90). The mortality reduction was evident in patients with baseline CD4+ cell counts less than 50 cells/µL (HR: 0.60; 95% CI: 0.54–0.67), 50–99 cells/µL (HR: 0.66; 95% CI: 0.56–0.78) and 100–199 cells/µL (HR: 0.78; 95% CI: 0.62–0.98). Conclusion Cotrimoxazole prophylaxis started early during ART reduced mortality and should be offered to HIV-infected patients in low- and middle-income countries.